DETEKSI DINI KANKER SERVIK PADA WANITA USIA SUBUR DENGAN INSPEKSI VISUAL ASAM ASETAT (IVA TEST) DI KLINIK BERSALIN KOTA MEDAN - Diah Lestari Nasution; Nur Asnah Sitohang; Cut Adeya Adella (Jurnal Riset Hesti Medan, 2018)
Cervical cancer in Indonesia ranks first, 65% of the patient's condition is in an advanced stage. In research in thirteen anatomical pathology laboratories in Indonesia, the frequency of cervical cancer patients was around 18.5%. This community service aims to: (1) provide communication, education and information (IEC) about cervical cancer and the benefits of IVA Test; (2) conduct IVA Test; (3) measure WUS's knowledge about cervical cancer and IVA test. Performed at the maternity clinic, namely SAM maternity clinic (20 people) and Sari (20 people). Data analysis using dependent t test. The results of the activity were data from 26-30 years old (40%), Batak tribes (13%), Islamic religion (95%), first marriage (77.5%), high school / diploma / undergraduate education (80%), IRT (77.5 %), the work of husband's employee (52.5%), first age married 26-30 years (40%) and not smoking (80%); using injection contraception (42.5%); the obstetric history of the majority of WUS giving birth twice (42.5%) , never checked (80%), no brother is sick (75%), breast cancer (10%), not much vaginal discharge (65%), no pain under the abdomen (70%), no bleeding during intercourse (90%) and did not experience irregular menstruation (55%); results of IVA WUS Test were negative (80%), inflammation (17.5) and positive (2.5); WUS knowledge before being given Information Education Communication (IEC) about cervical cancer and the IVA Test averages = 13.58, SD = 3.012 and after being given health education on average = 14.30, SD = 3.275. The results of statistical tests obtained different mean = 0.725 and P value = 0.016, it can be concluded that there was a significant effect of IEC on WUS knowledge about cervical cancer and IVA Test.      Keywords: Cervical cancer, fertile age women (WUS), IVA Test